Performance of Two Rape (Brassica napus) Cultivars under Different Fertilizer Management Levels in the Smallholder Sector of Zimbabwe - S. Ganya; E. Svotwa; R. D. Katsaruware (International Journal of Agronomy)
Crop response to fertilizer application depends on the physiological and morphological characteristics of the cultivars, thus causing cultivar differences in growth rate and final yield. A study was carried out in the Zvimba smallholder farming area of Zimbabwe, from November 2016 to February 2017, to investigate the performance of two rape (Brassica napus) cultivars under different nitrogen fertilizer management levels. An experiment was set up in a randomized complete block design, replicated three times, with two rape varieties, Hobson and English Giant, and 5 ammonium nitrate (AN) (34.5% N) fertilizer application rates (200 kg/ha, 300 kg/ha, 350 kg/ha, and 400 kg/ha) as factors. Nitrogen fertilizer rates had a significant (p<0.05) effect on leaf length at 6 WAP and 7 WAP. Nitrogen fertilizer application levels had significant effects on both in-season and total fresh leaf yield. There were no varietal effects on the leaf length (p>0.05), in-season yield and total leaf yield (p>0.05), and there were also no variety ∗ fertilizer application level interaction effects on leaf length, in-season yield and total leaf yield (p>0.05). From the results of this study, English Giant rape would maintain a longer leaf length than Hobson up to the end of the season, but the two cultivars have similar yield response to fertilizers’ application rate. Both the English Giant rape and Hobson rape cultivars can, therefore, be recommended for production in the Mhondoro smallholder farming area of Zimbabwe and other areas with similar climatic and soil characteristics.